2010
DOI: 10.3390/ijms11052056
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Protective Effect of Glibenclamide and Metformin in Combination with Honey in Pancreas of Streptozotocin-Induced Diabetic Rats

Abstract: Hyperglycemia exerts toxic effects on the pancreatic β-cells. This study investigated the hypothesis that the common antidiabetic drugs glibenclamide and metformin, in combination with tualang honey, offer additional protection for the pancreas of streptozotocin (STZ)-induced diabetic rats against oxidative stress and damage. Diabetes was induced in male Sprague Dawley rats by a single dose of STZ (60 mg/kg; ip). Diabetic rats had significantly elevated levels of lipid peroxidation (TBARS), up-regulated activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 29 publications
(31 reference statements)
13
89
3
1
Order By: Relevance
“…Other studies have also demonstrated that honey is able to increase antioxidant enzymes levels and ameliorate oxidative stress in plasma and other tissues such as renal and pancreas [61][62][63][64][65][66][67][68]. It is suggested that the aforementioned flavonoids contents and enzymatic and non-enzymatic substances in honey are responsible for its antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that honey is able to increase antioxidant enzymes levels and ameliorate oxidative stress in plasma and other tissues such as renal and pancreas [61][62][63][64][65][66][67][68]. It is suggested that the aforementioned flavonoids contents and enzymatic and non-enzymatic substances in honey are responsible for its antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the result of lower amount of free radicals available to activate the antioxidant enzymes as shown by reduction in oxidative DNA damage among the supplemented subjects. This also indicates that honey attenuates the changes in antioxidant enzymes in response to oxidant generation (EREJUWA et al, 2010).…”
Section: Antioxidant Enzymementioning
confidence: 92%
“…Honey is one of the natural food products that is well-known for its high nutritional and prophylactic medicinal value (PYRZYNSKA & BIESAGA, 2009). The antioxidative properties in honey have been proven effective in aiding the healing process of wounds and burns, diabetic ulcers, cancer, cardiovascular and neural diseases (TAN et al, 2009;EREJUWA et al, 2010;KHALIL et al, 2010). In addition, honey also helps to improve spatial memory and reduces the anxiety in aging mice, and has antimicrobial properties that act effectively against human pathogenic microorganisms (PAUL et al, 2007;CHEPULIS et al, 2009).…”
Section: Effect Of Nenas Honey Supplementation On the Oxidative Statumentioning
confidence: 99%
See 1 more Smart Citation
“…Tualang honey (TH) is a wild honey harvested from Tualang trees found in many Asian rainforests. Various studies have been conducted in an effort to evaluate the possible medicinal uses of TH [18][19][20][21][22][23][24]. One of the proposed therapeutic values is attributed partly due to its antioxidant properties.…”
mentioning
confidence: 99%